2017
DOI: 10.1016/j.tiv.2016.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of SLC drug transporter activities by environmental bisphenols

Abstract: The plastic component bisphenol A (BPA) is suspected to exert deleterious effects towards human health and targets various cellular and molecular pathways, including activity of ATP-binding cassette drug transporters. The present study was designed to determine whether BPA and some derivatives, like its substitutes bisphenol F (BPF) and bisphenol S (BPS) and the flame retardant tetrabromobisphenol A (TBBPA), may additionally interact with solute carrier (SLC) drug transporters. Activities of the various follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 65 publications
(44 reference statements)
1
9
0
Order By: Relevance
“…In summary, HAAs were shown to inhibit activities of OCTs in vitro, without, at least for Trp-P-1 and Trp-P-2, being transported by OCT1 and OCT2. Such data support the conclusion that interactions with membrane transporters are not restricted to drugs, but also concern environmental chemical contaminants like HAAs, bisphenols (Bruyere et al, 2017) or pesticides (Bain and LeBlanc, 1996;Chedik et al, 2017). The in vivo relevance of pollutants-mediated inhibition of transporter activities remains however challenged by the fact that human exposure to most of pollutants may result in tissue and blood levels of pollutants probably too low to be active on in vivo drug transporter activities.…”
Section: Accepted Manuscriptsupporting
confidence: 61%
“…In summary, HAAs were shown to inhibit activities of OCTs in vitro, without, at least for Trp-P-1 and Trp-P-2, being transported by OCT1 and OCT2. Such data support the conclusion that interactions with membrane transporters are not restricted to drugs, but also concern environmental chemical contaminants like HAAs, bisphenols (Bruyere et al, 2017) or pesticides (Bain and LeBlanc, 1996;Chedik et al, 2017). The in vivo relevance of pollutants-mediated inhibition of transporter activities remains however challenged by the fact that human exposure to most of pollutants may result in tissue and blood levels of pollutants probably too low to be active on in vivo drug transporter activities.…”
Section: Accepted Manuscriptsupporting
confidence: 61%
“…[26]) nor BSP (OATP inhibitor according to Ref. [19]) had any impact on TAC accumulation in our experiments, suggesting that these transporters are not involved in TAC uptake in PBMC. Again, the choice of these inhibitors could be discussed since probenecid can also inhibit MRP efflux protein [27,28].…”
Section: Discussionmentioning
confidence: 60%
“…In transporter inhibition experiments, the concentration of inhibitors is a critical parameter, which can strongly impact the results. In our study, we chose the concentrations of inhibitors according to the literature and in particular according to Ki reported for P‐gp . We used concentrations above the Ki of the inhibitors for P‐gp.…”
Section: Discussionmentioning
confidence: 99%
“…Although the complete molecular mechanisms that underlie additive and synergistic effects (Pivcevic and Zaja 2006) are complex, the presence of TICs could specifically affect the net uptake and accumulation of certain environmental chemicals of interest ( Figure 5). For instance, the environmental chemicals and endocrine disruptors BPA, perfluorooctanoic acid (PFOA), and zearalenone (ZEN) have been shown to be transported by breast cancer resistance protein (BCRP) (Mazur et al 2012;Dankers et al 2013;Bruyere et al 2017) and inhibition of BCRP could, in turn, promote EDC and toxic substrate accumulation. Therefore, drug transporter inhibition is another key event -along with non-monotonic dose−response, synergism of single non-lethal concentrations of chemicals, and interaction with other environmental stressors -necessary to predict toxicity and assess the risks of environmental chemicals.…”
Section: Approaches Used To Understand Effects Of Chemical Mixtures Amentioning
confidence: 99%
“…In addition, studies that evaluate how climate change affects this mixture reported that not only are alterations observed in the hypothalamic-pituitary-gonadal (HPG) axis, but Inhibition of ABC and SLC transporters can lead to higher accumulation of both the inhibiting environmental chemical and other toxic substrates otherwise expelled from the cells. (According to the results from Kleinow et al 2004;Dankers et al 2013;Nicklisch et al 2016;Bruyere et al, 2017;Chedik et al 2018) the hypothalamic-pituitary-thyroid (HPT) axis may also play a significant role. Tying together the individual AOPs for the individual compounds with and without APE/AP predictions can be made to justify in vivo mixture interactions.…”
Section: Approaches Used To Understand Effects Of Chemical Mixtures Amentioning
confidence: 99%